Six months of different exercise type in sedentary primary schoolchildren: impact on physical fitness and saliva microbiota composition - Mancini, Annamaria; Vitucci, Daniela; Lasorsa, Vito Alessandro; Lupo, Corrado; Brustio, Paolo Riccardo; Capasso, Mario; Orrù, Stefania; Rainoldi, Alberto; Schena, Federico; Buono, Pasqualina (Frontiers in Nutrition, 2024)
Lifestyle influences microbiota composition. We previously reported a healthier microbiota composition in saliva from active schoolchildren compared to sedentary. In the present study, we evaluated the effects of 6 months of different exercise types on physical fitness and saliva microbiota composition in 8-11-years-old sedentary schoolchildren. Methods: Sixty-four sedentary children from five primary schools in Turin, Italy, were divided into three groups: one continued normal curricular activity while two underwent different exercise protocols for six months. The Structured Exercise (Sa) group did 2 hours per week of muscle activation, strength and coordination exercises supervised by a kinesiologist. The Daily Mile (Dm) group did 1 hour per week of Sa plus 15 minutes of walking/running outdoors four times a week, supervised by a class teacher; control group (Ct) did 2 hour a week of curricular exercise supervised by a class teacher. Physical fitness was evaluated before and after the intervention. Saliva samples were collected postintervention in all participants and analyzed using PCR amplification of 16S rRNA bacterial genes. The Amplicon Sequence Variants were filtered, decontaminated, and phylogenetically classified using DADA2 software. Differential abundance analysis of microbiome taxa and pathway data was conducted using the LEfSe algorithm and PICRUSt. Results: The Sa group showed better performances in lower limb power and sprint performance while both the Sa and Dm groups improved in endurance and balance at the end of the intervention; only balance resulted slightly improved in the Ct group. Among the genera differently enriched in saliva after the training intervention, we found that the Prevotella, the Dubosiella and the Family XIII AD3011 group were the most abundant in the Sa group; differently, the Neisseria and the Abiotrophia in Ct group. Four species showed significant results: the Prevotella melaninogenica and the Prevotella nanceiensis were more abundant in the Sa, conversely, Gemella sanguinis was enriched in Dm and Abiotrophia defectiva in Ct saliva group.We demonstrated that Sa and Dm, not curricular exercise, improve the physical fitness components in sedentary schoolchildren correlated to health and promote an enrichment in saliva microbiota species associated to a healthier profile.